A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States - Taylor, Christopher A.; Robison, Henry W. (Zootaxa, 2016)
A new primary burrowing crayfish, Fallicambarus schusteri, is described from the Red River drainage of extreme southeastern Oklahoma and southwestern Arkansas and is placed in the subgenus Fallicambarus. The species occurs in roadside ditches that seasonally flood and have silt and silt-loam dominated soils. Falllicambarus schusteri differs from all other members of the genus Fallicambarus in possessing a thin gradually tapering central projection and a wide triangular cephalic process on the first pleopod of form I males, a sufflamen on the cheliped, and an antennal scale that is widest at its midpoint.